My family and other animals - Durrell, Gerald (Oxford University Press, 2003)
The weather in England that summer had been so awful that Gerald's mother sold the family house and took her children to live on the Mediterranean island of Corfu. Between lessons, the ten-year-old Gerald was free to walk round the sunny island and discover the wonderful people and animals living there. This is the story of Gerald's adventures with the fascinating animals of Corfu, and, of course, with his surprising family and their friends